The Exploration of Tik-Tok App to Teaching Speaking at the Eleventh Grade Students - Saputri, Kurnia; Marliasari, Sherly; Budiyanto, Darmawan (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Digital platforms have become increasingly integrated into educational practices in recent years in order to improve learning outcomes. TikTok, a popular social media app, offers unique opportunities for language learning, particularly in developing speaking skills. This study investigates the effectiveness of using TikTok as a tool for teaching speaking to eleventh-grade students at SMA N 2 Palembang. Objective: The primary aim of this research is to explore the impact of TikTok on students' speaking skills, engagement, and motivation in the learning process. The study also examines the potential challenges and benefits of integrating TikTok into language teaching. A mixed-methods approach was employed, combining quantitative and qualitative data. The sample comprised 250 eleventh-grade students who participated in a pre- and post-intervention speaking test. Additionally, a questionnaire was administered to gather data on student engagement and motivation. In-depth interviews with 10 students provided qualitative insights into their experiences. Quantitative data were analysed using paired t-tests and ANOVA, while qualitative data were subjected to thematic analysis. The quantitative analysis revealed a significant improvement in students' speaking test scores from pre-test (M = 65.3, SD = 10.4) to post-test (M = 75.8, SD = 8.7), with a mean difference of 10.5 points (t(249) = 18.63, p < 0.001). The questionnaire results indicated high levels of engagement (M = 4.5, SD = 0.6) and motivation (M = 4.6, SD = 0.5). Qualitative findings highlighted increased student confidence, practical application of speaking skills, and the supportive role of peer feedback. However, challenges such as technical difficulties and potential distractions were noted. The integration of TikTok into language teaching significantly improves students' speaking skills and engagement. While challenges exist, they can be mitigated with careful planning and support. This research contributes to the growing body of literature on digital and social media integration in education, offering a novel approach to enhancing speaking proficiency in EFL learners.